Performance of samama (Anthocephalus macrophyllus) LVL based on veneer thickness, juvenile proportion and lay-up. Issue 3 (3rd May 2020) - Cahyono, Tekat Dwi; Darmawan, Wayan; Novriyanti, Eka
ABSTRACT: A study to determine the quality of laminated veneer lumber (LVL) from samama wood ( Anthocephalus macrophyllus ) was carried out. Samama is a fast-growing endemic wood in eastern Indonesia. Factorial of three factors in RAL design was used to investigate the influence of veneer thickness, juvenile proportion and veneer lay-up to the quality of the resulted samama LVL. The veneer thicknesses were 1.5 and 3.0 mm. Juvenile proportions were arranged in five levels, which were 100% of juvenile veneer, 100% of mature veneer and combination of both juvenile and mature with juvenile proportion of 14%, 43% and 71%. Two veneer lay-up used in this study were loose side met loose side and tight side met loose side. The result of the study showed various specific gravity of LVL by different proportions of juvenile. This factor also affected the other physical traits. Shear strength of the LVL was equal to the solid wood, yet MOE and MOR were affected by juvenile proportion and veneer lay-up. LVL developed from 100% of mature veneer exhibited the highest MOE and MOR, yet no significant difference was noted in MOE and MOR between LVL 100% of juvenile and other tested juvenile proportions.